Continuity of Care as a Final Project for Midwifery Diploma Students in Indonesia - Teta Puji Rahayu; Astin Nur Hanifah (Aloha International Journal of Health Advancement (AIJHA), 2019)
Continuity of Care as a Final Project for Midwifery Diploma Students in Indonesia